MOTL: enhancing multi-omics matrix factorization with transfer learning - Hirst DP; Térézol M; Cantini L; Villoutreix P; Vignes M; Baudot A (BioMed Central Ltd, 2025)
Joint matrix factorization is popular for extracting lower dimensional representations of multi-omics data but loses effectiveness with limited samples. Addressing this limitation, we introduce MOTL (Multi-Omics Transfer Learning), a framework that enhances MOFA (Multi-Omics Factor Analysis) by inferring latent factors for small multi-omics target datasets with respect to those inferred from a large heterogeneous learning dataset. We evaluate MOTL by designing simulated and real data protocols and demonstrate that MOTL improves the factorization of limited-sample multi-omics datasets when compared to factorization without transfer learning. When applied to actual glioblastoma samples, MOTL enhances delineation of cancer status and subtype.
Keywords: Matrix factorization; Dimensionality reduction; Multi-omics; Data integration; Transfer learning; MOFA